2019
DOI: 10.1002/jcp.28916
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐210‐3p inhibits osteogenic differentiation and promotes adipogenic differentiation correlated with Wnt signaling in ERα‐deficient rBMSCs

Abstract: MicroRNAs (miRNAs) regulate activities in living organisms through various signaling pathways and play important roles in the development and progression of osteoporosis.The balance between osteogenic and adipogenic differentiation of rBMSCs is closely related to the occurrence of osteoporosis. ERα regulates bone metabolism in various tissues. However, the correlation among ERα, miRNAs, and the differentiation of rBMSCs is still unclear. In this study, we used lentivirus transfection into rBMSCs to construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…This might be related to the complexity of the regulatory mechanism of cell differentiation. We have known that many proteins 45,46 and a lot of miRNAs 25,[47][48][49][50][51] have been reported to participate in adipogenic differentiation. Similarly, for angiogenesis, both proteins [52][53][54][55][56][57] and miRNAs [58][59][60] played a regulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the complexity of the regulatory mechanism of cell differentiation. We have known that many proteins 45,46 and a lot of miRNAs 25,[47][48][49][50][51] have been reported to participate in adipogenic differentiation. Similarly, for angiogenesis, both proteins [52][53][54][55][56][57] and miRNAs [58][59][60] played a regulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bone diseases, the proportion of adipocytes is often increased concomitant with a decrease of BMSCs that could differentiate into osteoblasts. 37,38 Studies increasingly demonstrated the involvement of lncRNAs in osteogenic and adipogenic differentiation of BMSCs. Shuai Figure 4 Osteogenic differentiation of BMSCs was inhibited by overexpression of HOTAIR and enhanced by siHOTAIR.…”
Section: Dovepressmentioning
confidence: 99%
“…Among the 10 miRNAs that changed in both ASCs and BMSCs upon osteoblastic differentiation, miR-210-3p and miR-335-3p were down-regulated and had relatively higher expression than the other down-regulated miRNAs in ASCs and BMSCs ( Table 1 ). In our previous study, these two miRNAs were also down-regulated and acted as negative regulators of osteoblastogenesis [ 40 ] and other studies have supported a role for these two miRNAs in osteoblastogenesis [ 42 , 43 ]. Notably, most of the miRNAs with significantly differential expression were cell origin specific: 47 miRNAs were only differentially expressed in ASCs and 25 miRNAs only in BMSCs.…”
Section: Discussionmentioning
confidence: 85%